2014
DOI: 10.1186/1869-5760-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal bulging in patients with Vogt-Koyanagi-Harada disease in the non-acute uveitic stage

Abstract: BackgroundDetection of choroidal inflammation in Vogt-Koyanagi-Harada (VKH) disease is still a challenge. Progression to sunset glow fundus has been observed despite apparent good clinical control of inflammation. Indocyanine green angiography (ICGA) permits choroid inflammation detection, though it is invasive, time consuming, and costly. The purpose of the present study is to report a sign indicative of probable inflammation on enhanced depth imaging spectral-domain optical coherence tomography (EDI-OCT): a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…In the present study, we revealed that the choroid also thickened during the anterior segment recurrence without any obvious findings in the posterior segment, and that this choroidal thickening had already been observed 1 month before detecting the recurrence. Although choroidal thickness alterations without any funduscopic findings have been examined in a few case reports,15 16 this study is the first case series to describe the detailed sequential changes in choroidal thickness in relation to the anterior recurrence of VKH disease.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, we revealed that the choroid also thickened during the anterior segment recurrence without any obvious findings in the posterior segment, and that this choroidal thickening had already been observed 1 month before detecting the recurrence. Although choroidal thickness alterations without any funduscopic findings have been examined in a few case reports,15 16 this study is the first case series to describe the detailed sequential changes in choroidal thickness in relation to the anterior recurrence of VKH disease.…”
Section: Discussionmentioning
confidence: 98%
“…An increase in choroidal thickness of >100 μm during corticosteroid tapering, even in the presence of apparently good clinical control, has been defined as rebound choroidal thickening suggesting recurrent subclinical inflammation 117. While this can be accompanied by other ocular signs, such as anterior chamber cells and/or optic disc hyperfluorescence on FFA and/or dark dots on ICG,119 it can also precede them 47. Rebound choroidal thickening on EDI-OCT was the only sign of ocular inflammation in a 71-year-old patient who presented 6 months after his initial diagnosis with headache, tinnitus, and bilateral sensorineural hearing loss 120.…”
Section: Historical Aspects and Epidemiologymentioning
confidence: 99%
“…Ocular coherence tomography confirmed the presence of both serous retinal and PEDs and revealed irregular undulations of the retinal pigment epithelium (RPE) due to acute inflammatory thickening of the choroid and typical for the acute uveitic phase of VKH disease. 5,[27][28][29][30] Neither enhanced depth imaging nor indocyanine green angiography was performed. The patient responded to treatment with high dose systemic prednisone followed by a transition to azathioprine with reversal of all ocular complications and had no recurrences with 1 year of follow-up.…”
mentioning
confidence: 99%